P73 The complexities of defining atopy in severe childhood asthma. (16th November 2010) - Frith, J; Fleming, L; Bossley, C; Ullmann, N; Bush, A
Abstract : Background: Defining atopy in children with severe therapy resistant asthma is complex. There is currently no gold standard test; skin prick testing (SPT) and allergen specific immunoglobulin E (sIgE) are both used. Atopy is increasingly considered to be a spectrum, not an all-or-none phenomenon (Allergy 2007;62 :1379–86). Hypothesis: SPTs and sIgE cannot be used interchangeably, and that if both tests are not performed opportunities for intervention will be missed. Furthermore, severity of atopy will be defined differently by the two tests. Total IgE and fractional exhaled nitric oxide (FeNO50 ) may also help quantify atopy. Methods: Cross-sectional study of 47 children with severe therapy resistant asthma, mean age 11.8 years (range 5.3–16.6 years) who underwent measurement of a standard panel (house dust mite (HDM), dog, cat, weed pollens and grass pollens) of SPTs and sIgEs, total IgE and FeNO50 as part of their clinical work up. Results: Overall 42/47 (89%) were atopic (defined as either a single positive SPT or sIgE). There was 98% concordance between the two tests in classifying atopy. When each allergen was considered individually, in 40/201 (19.8%) the SPT and sIgE results were discordant (Abstract P73 Figure 1 ), most commonly, 25/201 (12.4%) the SPT was negative and the sIgE was positive. HDM and cat sensitisation were more likely detected by sIgE, but dog by SPT. When atopy was quantified the sum of sIgEs compared with the sum of SPT wheal diameter showed only moderate correlation (r=0.66, p=<0.001). Total IgE increased with an increasing number of positive sIgEs (p=0.028), but not significantly with number of positive SPTs. There was a significant correlation between FeNO50 and total IgE (r=0.34, p=0.02), but no difference in FeNO50 when patients were defined as atopic on either SPT or sIgE, and no relationship with increasing numbers of positive SPTs or sIgEs. Conclusions: SPT and sIgE identify the group prevalence of atopy equally well; however for some allergens, concordance is poor, and when used to quantify atopy SPT and sIgE show only moderate correlation. If allergen avoidance is contemplated in children with severe therapy resistant asthma, then both tests should be performed in order to detect sensitisation.